Association of Cardiac Autonomic Function Derangement with Obesity and Glycated Haemoglobin: A Cross-sectional Study - Piyush Bansal; Prerna Panjeta; Praveen Prashant; Komal (Journal of Clinical and Diagnostic Research, 2023)
Introduction: Hyperglycaemia (as assessed by Glycated haemoglobin (HbA1c)) and obesity lead to the production of advanced glycation end products in blood, which are responsible for damage to the microvasculature, slowly leading to cardiac autonomic dysfunction. Thus, chronic prediabetic hyperglycaemia, as measured by HbA1c may affect cardiac autonomic function in different ranges of obesity (overweight and obese). Aim: To study the association of cardiac autonomic dysfunction with Body Mass Index (BMI) and HbA1c. Materials and Methods: The cross-sectional study was conducted at BPS Government Medical College, Sonepat, Haryana, India, from June to December 2019. This study included age and sex-matched 50 healthy, 50 overweight, and 50 obese subjects aged 18-50 years. Serum HbA1c, lipid profile and cardiac autonomic function tests for the parasympathetic system (Resting heart rate, Expiration-inspiration difference on deep breathing, Heart rate response to standing/30:15 stand ratio, Valsalva ratio) and sympathetic system {postural hypotension/fall in Systolic Blood Pressure (SBP) and change in Diastolic Blood Pressure (DBP) on sustained hand grip test} were performed. Chi-square test and Mann-Whitney test were used for statistical analysis. Results: The prevalence of sympathetic autonomic dysfunction was highest in the obese group (36% in males n=25, and 32% in females, n=25) followed by overweight group (12% in males, n=25 and 12% in females, n=25). The prevalence of parasympathetic autonomic dysfunction was highest in the obese group (40% in males, n=25 and 32% in females, n=25), followed by the overweight group (24% in males, n=25 and 16% in females, n=25). Further, HbA1c was highest in obese males (6.27±1.54) and females (5.94±0.45), followed by overweight males (5.89±0.92) and females (5.46±1.84). Males and females with autonomic dysfunction had significantly higher HbA1c (Males 6.4±0.42 and Females 6.2±0.38) than those without it (Males 5.4±0.86 and Females 5.2±0.75) in the obese and overweight groups taken together. Conclusion: The prevalence of parasympathetic and sympathetic dysfunction is incrementally increased with higher obesity (BMI) and HbA1c. Overweight and obese subjects with cardiac autonomic dysfunction had higher HbA1c and worse lipid profiles than overweight and obese subjects without autonomic dysfunction.